Parenteralno dajanje zdravil - intramuskularna injekcija - Šmitek, Jana (Obzornik zdravstvene nege, 2005)
The article presents the reasons for parenteral drug application, its characteristics and methods of different drug applications. Intramuscular injection is presented in detail. Most common problems and side effects of muscular and subcutaneous drug application are presented as well.
Keywords: drug; Injections, Intramuscular; Injections, Intravenous; Injections, Subcutaneous; injekcije; Injekcije intramuskularne; Injekcije intravenske; Injekcije subkutane; Nursing Care; zapleti; zdravila; Zdravstvena nega